Adaptive governance in mitigating hydrometeorological disaster risk in Sinjai Regency - Abd Haris; Sumardi (Publisia: Jurnal Ilmu Administrasi Publik, 2025)
This research aims to identify factors that influence the level of vulnerability and risk of hydrometeorological disasters in Sinjai Regency and formulate policies that can be implemented through an adaptive governance approach. This research uses qualitative data collection techniques, including interviews, documentation and field observations. The collected data was then analyzed using Nvivo 12 Plus analysis software. The findings of this study succeeded in mapping the factors that influence the level of vulnerability and risk to hydrometeorological disasters in Sinjai Regency. The topography includes lowlands at high risk of flooding and hills and mountains susceptible to landslides, coupled with climate change, which causes extreme rainfall intensity, increasing the risk of disasters in this region. Poor community preparedness and inadequate disaster management infrastructure exacerbate the impact of disasters, highlighting the need for improvements in early warning systems, drainage networks, and preparedness training. The application of adaptive governance principles, including multi-stakeholder involvement, continuous monitoring and evaluation, capacity development, and responsive spatial planning, is expected to increase the effectiveness of disaster risk mitigation, adapt strategies to local needs and changing environmental conditions, and strengthen collaboration to reduce vulnerability and increasing community resilience to the impacts of disasters in Sinjai Regency.